Beyond the Battery: The Impact of Cultural Factor on Electric Vehicle Consumers’ Service Quality Expectations in Dealerships - Yang Zhou; Wanwen Dai; Miao Xiao (World Electric Vehicle Journal)
This research investigates the impact of cultural dimensions on service quality expectations in electric vehicle (EV) dealerships. Grounded in Hofstede’s cultural theory and employing a data-driven approach, the study utilizes a series of robust analytical techniques, including the SVM algorithm, factor analysis, and ANOVA. Through a comprehensive analysis of EV customers’ expectations for expertise, empathy, and responsiveness, the findings reveal that cultural dimensions significantly shape service quality expectations, regardless of the service provider’s gender. Notably, consumers with a stronger masculine orientation have lower expectations for expertise but higher expectations for empathy than those with a stronger feminine orientation. These findings challenge the traditional emphasis on gender as a key factor in service quality expectations and underscore the need to incorporate cultural values in service strategy design and quality improvement in the EV industry.